Chemical constituents of Datura metel L. - Mai, Nguyen Thi; Cuc, Nguyen Thi; Quang, Tran Hong (Vietnam Journal of Chemistry, 2017)
Chemical investigation of an acidic methanol extract of the whole plant of Datura metel resulted in the isolation of seven compounds, including pterodontriol B (1), disciferitriol (2), scopolamine (3), adenosine (4), thymidine (5), ilekudinoside C (6), and dioscoroside D (7). Their structures were elucidated by extensive spectroscopic methods, including 1D and 2D NMR and mass spectra and in comparison with reported data in the literature. Among the isolated compounds, pterodontriol B, disciferitriol, ilekudinoside C, and dioscoroside D were reported for the first time from the Datura genus. Keywords. Datura metel, Solanaceae, sesquiterpene, triterpenoid saponin, steroidal saponin.